Simultaneous reinforcement of both rigidity and energy absorption of polyamide-based composites with hybrid continuous fibers by 3D printing. (1st July 2021) - Wang, Kui; Li, Shixian; Wu, Yiyun; Rao, Yanni; Peng, Yong
Abstract: The use of continuous fiber as reinforcement is well known to improve the mechanical performance of thermoplastic printed laminated composites. However, it is difficult to optimize the rigidity and energy absorption of continuous fiber reinforced composite components, since the inherent conflict between strength and ductility. For this purpose, this study focused on the design and characterization of continuous fibers reinforced polyamide (PA)-based composites, prepared via 3D printing, with synergistic enhancement of the strength and ductility. Continuous carbon and Kevlar fibers were used as reinforcements for production of printed non-hybrid and hybrid composites. The quasi-static indentation (QSI) test and structural evolutions analysis of composites were conducted to evaluate the mechanical properties and reveal the deformation and failure mechanisms. A Volume Average Stiffness (VAS) model and a hybrid effect model were introduced to predict the effective stiffness and to analyze the hybrid effect on the energy absorption capabilities of the printed hybrid composites, respectively. The results showed that the addition of the continuous carbon and Kevlar fibers with a certain designed improved toughness of the composite, which led to an enhancement of the energy absorption properties. The deformation and failure mechanisms of hybrid continuous fiber reinforced composites highly depended on the designed position of fibers. For the printed hybrid composites, the highest indentation force could be achieved when continuous Kevlar fiber layers were placed at the rear side. While the highest energy absorption capability of the printed composites was captured when continuous carbon fiber layers were positioned at the rear side.